Teacher preparation in Australia : history, policy and future directions - O'Donoghue, Thomas; Moore, Keith (Emerald studies in teacher preparation in national and global contexts, 2019)
Teacher policy and practice in Australia has evolved substantially from the development of the first colony in 1788 to the present. This book traces the history of teacher preparation through five inter-related phases; the unregulated phase, the apprenticeship phase, the ascendancy of the Teachers Colleges, the ascendancy of the Colleges of Advanced Education, and the university dominated phase from 1989 to the present day. While the focus is primarily on preparation to teach in primary and secondary schools, this important text also sheds light on teacher preparation for vocational education and at kindergarten level. The rich historical overview explores both the state and private sector together with that of the Christian Churches. Furthermore, research is not merely restricted just to initial teacher preparation; continuing professional development is also considered.With its comparative outlook, this book will prove an invaluable resource for not only Australian educational leaders, historians and policy makers, but also their counterparts internationally. The authors provide an exposition which will be used by teacher educators in many parts of the world to sharpen their perceptions of their own situations through comparison and contrast, to provoke ideas for critical discussion, and to stimulate them to come to an understanding of the importance of considering contemporary developments within their wider historical contexts.